Pregnancy after stillbirth and loss - Heazell, Alexander E. P. (Henry Stewart Talks, 2024)
Complications in previous pregnancy, Pregnancies after stillbirth, Recurrence of complications, Rainbow Clinic, Care in subsequent pregnancies, Interventions in subsequent pregnancies